Effects of disrupting insulin-like growth factor-1 receptor (IGF-1R) signal transduction pathways with inhibitors of IGF-1R, EGFR, PI3K, MEK, and MTOR in breast cancer cell lines - Ayub, Ayunadirah (2014)
Insulin-like growth factor receptor 1 (IGF-1R) has been shown to be overexpressed in patients with breast cancer. IGF-1R signaling pathway is known to activate numerous kinases, and proteins associated with cell growth and survival. Targeting these kinases and their pathways are promising therapeutic approaches compared to disruption of IGF-1R alone. The general objective of this study was to determine the appropriate combination of small molecules inhibitors which can synergize to inhibit the activation of IGF-1R and its downstream pathways in order to decrease the viability and growth of breast cancer cell lines. The specific objectives of this study were (i) to determine the effect of IGF-1R inhibitor (NVP-AEW541) and EGFR inhibitor (Gefitinib) on the viability of breast cancer cells, (ii) to determine the effects of KU0063794 (MTOR inhibitor), PD0325901 (MEK inhibitor), and NVP-BKM120 (PI3K inhibitor) which are small molecule inhibitors that target the downstream molecules of IGF-1R pathway on breast cancer cell viability, and (iii) to determine the efficacy of inhibitor combinations on cell viability, apoptosis, cell cycle, and the expression of phosphorylated biomolecules related to the targeted signaling pathways. Combinations of several inhibitors (NVP-AEW541, KU0063794, PD0325901, NVPBKM120, and Gefitinib, simplified as AEW, KU, PD, BKM, and Gefitinib) that target different molecules in the IGF-1R pathway were compared with single (mono) inhibitor treatment. All combinations tested on MCF-7 and MDA-MB-231 cells can induced cell apoptosis and G1 and G2/M phase arrest. Furthermore, BKM+AEW, KU+BKM, and KU+AEW exhibited cytotoxic activity in MCF-7, while KU+AEW, PD+BKM, PD+KU, and PD+AEW led to complete cytostasis in MDA-MB-231 cells. The inhibitors also inhibited the activation of IGF-1R and its downstream pathways (PI3K/AKT, MTOR, MAPK/ERK), but there were exceptional new findings on the effects of BKM on MAPK/ERK pathway and PD on PI3K/AKT pathway in breast cancer cell lines. The blockade of PI3K/AKT pathway by PI3K inhibitor (BKM) caused activation of MAPK/ERK pathway. However, the blockade of MAPK/ERK pathway by MEK inhibitor (PD) leads to activation of PI3K/AKT pathway through a negative feedback loop between PI3K/AKT and MAPK/ERK pathways. This study reveals that combination between KU and AEW exerted the most significant synergistic effect on growth inhibition of MCF-7 cells, whereas the most significant synergistic effect were found with PD and AEW in MDA-MB-231 cells. These two combinations yield the most significant synergistic effect on growth inhibition of the cells by blocking the IGF-1R downstream pathways which causes decreased in growth rate, induction of apoptosis, and cell cycle arrest. In addition, to the best of our knowledge, targeting MTOR and IGF-1R pathways by using KU and AEW is a potential new combination therapeutic strategy for breast cancer. The strategy of targeting IGF-1R pathway and its downstream molecules for breast cancer therapy is useful as they can exert synergism to reduce cell viability and to induce apoptosis and cell cycle arrest in breast cancer cells. The combination of inhibitors can also inhibit the activation of IGF-1R downstream pathways that may provide a therapeutic benefit in treating breast cancer through the pathways feedback as described in this study.